A Mother’s Unconditional Love: Experience of a Person’s Deprived of Liberty (PDL) - John Michael Del Rosario Aquino (Universitas Ahmad Dahlan, 2023)
The researcher intends to retell and comprehend the story of a mother in Bureau of Corrections using a narrative approach whose life choices reflect the unconditional love she has for her imprisoned children. The researcher is interested in the obstacles encountered and coping mechanisms used to survive behind bars, as well as any life lessons. The research participant was chosen employing purposive sampling. The researcher validated and pilot-tested the guide questionnaire. There are both positive and negative events that challenge her to survive and overcome all of the obstacles. The absence of family, the availability of food, and the management system of BuCor. Nonetheless, these challenges are surmountable. Similarly, as PDL's mother participated in numerous BuCor activities, she was able to gain profound insight and reflect on her conduct. She has sacrificed her life, no regrets in life in order for her children to survive.